Motivational Strategies Applied by the English Tutors to Teach Young Learners - Rabiatul Adawiyah (Fakultas Sastra - Universitas Muslim Indonesia, 2022)
Young learners’ characters are different from adolescents and adults so their teachers need to apply some strategies to motivate them for studying English well. Some children’s motivated behavior such as high attention and participation in learning appeared at an English course institution in Palangka Raya, GLC. Therefore, this study aimed to describe the motivational strategies applied by the English tutors of GLC to teach young learners. The study used a qualitative approach with a case study. In collecting the data, it used observation, interviews, and documentation. The research findings showed when it was related to the motivational strategies in teaching English based on Dornyei, two tutors of GLC applied four aspects of motivational strategies. They were creating the basic motivational conditions, generating initial motivation, maintaining and protecting motivation, and then encouraging positive retrospective self-evaluation. These strategies were applied in the learning process to bring out, preserve, and enhance their motivation.